The Promise of One Safe Future for the Oplan Likas Resettled Families of Metro Manila - Quetulio-Navarra, Melissa (Archīum Ateneo, 2025)
This study examines the impacts of the Philippine government’s resettlement approach and resettlement programme on the well-being of the displaced poor families due to the implementation of the Philippine government climate change adaptation programme affecting an estimated 11,400 families residing on top and along major rivers and connecting waterways within Metro Manila. Overall, the resettlement programme comprised of social preparation, inter-governmental involvement, financial assistance, and distant and in-city resettlement has failed to deliver on the promise of One Safe Future to the former informal settlers living on Metro Manila waterways and instead rendered them worse-off in all areas of economic, social and psychological well-being. The social preparation process was tokenistic, financial assistance became a reverse incentive for the families, and in the general scheme of Oplan Likas resettlement programme, compared with in-city resettled families, families in off-site relocation sites are in worse situations and suffer even more due to site location, poorly constructed housing units, lack of basic and social services that altogether create irreversible damage to the welfare of the residents, both the adults and children. It is therefore noteworthy for the government to find ways how to mainstream and scale the community-led approach, an alternative housing modality to accommodate the housing needs of the country’s ISFs with a promise of a bright future.